2008
DOI: 10.1161/circimaging.108.781120
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-Based Matrices Improve the Delivery of Transplanted Circulating Progenitor Cells

Abstract: Background-Collagen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…34 In addition, the low engraftment and survival 35 of transplanted cells limit their benefits. In this regard, we have previously demonstrated by tracking cells with PET and by histology that our collagen-based matrix can improve cell retention and prevent excessive relocation of transplanted cells to nontarget tissues, 36 in addition to improving capillary density. 14 We also previously showed that CACs exposed to the matrix demonstrated higher levels of phosphorylated Akt (PI3K/Akt pathway) and increased survival under hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…34 In addition, the low engraftment and survival 35 of transplanted cells limit their benefits. In this regard, we have previously demonstrated by tracking cells with PET and by histology that our collagen-based matrix can improve cell retention and prevent excessive relocation of transplanted cells to nontarget tissues, 36 in addition to improving capillary density. 14 We also previously showed that CACs exposed to the matrix demonstrated higher levels of phosphorylated Akt (PI3K/Akt pathway) and increased survival under hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, no relocated cells were found in the liver of animals receiving this combination treatment, which is, however, normally a sink for the relocation of injected cells [328]. Similarly, another study demonstrated improved early engraftment and directed localization of transplanted endothelial progenitor cells (EPCs) post-transplantation via enhancing progenitor cell retention and limiting distribution to nonspecific tissues when the cells were impregnated in an injectable collagen matrix [329]. ECM-mimetic hydrogels containing the collagen I-derived peptide GPQGIAGQ were also demonstrated to induce endothelial cell adhesion and capillary-like network formation [330].…”
Section: Human Tissue Ecm-based Biomaterialsmentioning
confidence: 99%
“…Chitosan and collagen are naturally derived, biodegradable, biocompatible polymers that have been explored for their potential use in tissue engineering [13,[28][29][30][31][32]. To improve upon the resulting hydrogel mechanical properties, it is common for these compounds, either alone or in combination, to be cross-linked using exogenous (occasionally toxic) chemical cross-linkers [28,33,34].…”
Section: Hydrogel Formationmentioning
confidence: 99%